The Effects of Two Different Concurrent Training Configurations on Markers of Metabolic Syndrome and Fitness in Women With Severe/Morbid Obesity: A Randomised Controlled Trial - Delgado-Floody, Pedro; Soriano-Maldonado, Alberto; Rodríguez-Pérez, Manuel A.; Latorre-Román, Pedro Ángel; Martínez-Salazar, Cristian; Vargas, Claudia Andrea; Caamaño-Navarrete, Felipe; Jerez-Mayorga, Daniel; Álvarez, Cristian (Frontiers in Physiology, 2021)
Concurrent training (CT, characterized by the inclusion of two exercise modalities), is recognized to improve metabolic syndrome (MetS) markers, but little is known about the order session effect on interindividual variability. The purpose of the present study was to describe the effects, and the interindividual variability, of 20 weeks CT in a different order (i.e., high-intensity interval training (HIIT) plus resistance training (RT), compared with another group doing RT plus HIIT) in women with severe/morbidly obesity at risk of MetS. Overall, 26 women with morbid obesity were assigned to either a HIIT+RT group [n=14, mean and 95%CI, 45.79 (40.74; 50.83) or to RT+HIIT group (n=12, 33.6 (25.30; 41.79 years]. MetS main outcomes were waist circumference (WC, cm), systolic (SBP, mmHg) and diastolic blood pressure (DBP, mmHg), high-density lipoprotein cholesterol (HDL-c), triglycerides (Tg), and fasting plasma glucose (FPG). Secondary outcomes were other anthropometric, body composition, lipids, muscle strength, and the six-minute walking test (6Mwt). There were significant differences in the prevalence of nonresponders (NRs) only for WC comparing HIIT+RT 2 (18.1%) vs. RT+HIIT group 5 (50.0%), at p < 0.0001, but not for SBP 4 (27.2%) vs. 4 (40.0%), DBP 8 (72.7%) vs. 7 (70.0%), FPG 8 (72.7%) vs. 9 (90.0%), HDL-c 7 (63.6%) vs. 8 (80.0%), and Tg 7 (63.6%) vs. 8 (80.0%). Additionally, the RT+HIIT group showed significant reductions in WC (∆ –3.84 cm, p = 0.015), SBP (∆ –8.46 mmHg, p = 0.040), where the HIIT+RT group elicited significant reductions only in SBP (∆ –8.43 mmHg, p = 0.022). The HIIT+RT promoted a lower prevalence of NRs than the RT+HIIT order session on WC, and overall, there was a slight advantage in the RT+HIIT group which favored more beneficial training-induced effects